Virtual Reality Film Development: Immersive, Cinematographic, and Duration - Fitriati, Trimalda Nur; Rahma, Dea Wemona; Firman, Reza Ramadani; Cahyani, Aisyah (Journal of Informatics and Communication Technology (JICT), 2023)
The film industry is growing rapidly. Nowadays, there are movies with 360 video format or also called virtual reality movies. This type of film provides a new experience for the audience because it can provide a sense of immersion. Immersion is the emotional feeling of being “in” in an experience. An immersive experience makes the audience feel as if they are involved in the story or image that is being displayed. It's no longer just watching it. Unfortunately, immersion in VR films also has a weakness, which can cause the audience to lose focus on the storyline. Using VR media for too long can cause health problems. Therefore, this study aims to determine the immersive experience, duration, and cinematographic aspects that are effectively applied to VR films. The point is that the story shown can be conveyed properly to the audience, and the audience feels comfortable. The method used in this research is a qualitative method with a literature study approach. There are 8 articles used as references in this study. The findings from this study are that the immersion of VR films can be increased by using the right media, namely HMD. 20 minutes is the maximum duration for viewers to enjoy VR films without worrying about health risks. The focus of the audience can be directed by cinematographic aspects such as composition, light, point of view, and continuity